Variability of TOC and DBPs (THMs and HAA5) in drinking water sources and distribution system in drought season: the North Iran case study. Issue 1 (2nd January 2021) - Kalankesh, Laleh R.; Zazouli, Mohammad Ali; Susanto, Heru; Babanezhad, Esmaeil
ABSTRACT: The aim of this study is tracing seasonal variability of total organic carbon (TOC), trihalomethanes (THMs) and haloacetic acids (HAA5) as disinfection by-products (DBPs) in drinking water sources and the distribution system in the north of Iran. The results showed that the concentrations of TOC were within the range of 0.013–1.42 mg/L. In addition, the results showed that most of the water sources had nearly the same concentration level (i.e. <1 mg/L), with the exception of one peak for groundwater source and middle drinking water distribution system in the city of Sari (1.42 mg/L) and Babol (1.37 mg/L). It was demonstrated that brominated HAA (MBAA) presented the highest concentration in the Sari City (17.3 µg/L) followed by the City of Behshahr (8.9–11.19 µg/L). The Babol City showed the highest concentration of chlorinated HAA (22.403 and 22.503 µg/L for DCAA and TCAA, respectively). Among the different compounds of THMs, the concentration of CHBr3 was nearly in the same order of magnitude in the cities of Sari, Babol and Behshahr for both spring and summer seasons. The brominated THM (BDCM) concentrations were also high (14.7 µg/L) in the Behshahr City. The results of independent t -test indicated that the seasonal (spring and summer) difference was statistically significant in the case of temperature and TTHM ( p  < 0.05). Furthermore, total HAA5  ≤ 60 µg/L and THM ≤100 µg/L in all the considered cities over the period of the study. The TTHMs concentration was 56 µg/L in treating surface water (TSW) source in the summer season at the Sari city. GRAPHICAL ABSTRACT: UF0001